Interrelation and Mutual Influence Between the Legal Responsibility of Servicepersons and Other Types of Retrospective Social Responsibility - Gryhorenko, Ye. I. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article analyzes various aspects of the implementation of legal responsibility as a type of social responsibility of servicemen. The characteristics of the relationship and the interaction of legal responsibility with various types of retrospective social responsibility (without a legal component) of persons serving in the military are given. It indicates the specifics of the social and professional status of military personnel and its dependence not only on legal norms, but also on other social regulators, for the non-realization of which various types of retrospective social responsibility are provided. Examples are given of bringing servicemen to legal responsibility for the violation of not only legal norms, but also moral and other social norms.